EFFECT OF COGNITIVE RESTRUCTURING AND SOCIAL SKILLS TRAINING ON SOCIAL PHOBIA AMONG SECONDARY SCHOOL STUDENTS IN JEGA METROPOLIS, NIGERIA - MUZA, SHEHU HARUNA; KABIR, HAMISU MUHAMMAD (Sokoto Educational Review, 2025)
social phobia among secondary school students in Jega Metropolis. The study was guided by three objectives and tested three null hypotheses. A quasi-experimental design with pre-test and post-test on two experimental groups was utilized. The population consisted of 1,742 students exhibiting social phobia symptoms in Jega metropolis. A sample of 40 students was selected using purposive sampling. The Social Phobia Inventory (SPIN) with a reliability coefficient of 0.81 was used for data collection, and t-test statistics analyzed the data. Findings indicated that students exposed to CR and SST experienced a significant reduction in excessive social phobia (p=0.001, and p=0.000). Furthermore, a significant differential effect was observed between CR and SST (p=0.009), with SST being more effective. The study concluded that both CR and SST are effective in reducing social phobia, with SST being more potent. Psychologists and counselors were recommended to utilize these techniques to improve students' social interactions and learning competency. DOI: https://doie.org/10.10318/SER.2025955657